Relationship of Family Support and Referral Procedures for Delays in Maternal Emergency Referral at Tamiang Layang Hospital, East Barito Regency - Hesti Yuniastutiningsih, Diadjeng Setya Wardani, Novida Ariani (Pakistan Journal of Medical & Health Sciences, 2022)
The case of late referral is one of the main problems with maternal and infant mortality in Indonesia. The maternal mortality rate in Indonesia is at the highest position in Southeast Asia, at 305 per 100,000 live births. The concept of three models of procrastination is a determinant that has a considerable role in the occurrence of maternal death in society. These delays include being late in recognizing red flags and making decisions, being late in reaching health facilities, and being late in getting help. When a maternal emergency occurs, the rapid decision- making by the mother or family to decide on referral approval is a contributing factor to the success of medical interventions to prevent mortality. In addition, survival depends on the fast and appropriate initial management and implementation of referral procedures by the midwife or referring health center. This study aims to determine how the relationship between family support and referral procedures for delays in maternal emergency referrals with delays in decision making as intervening variables. This type of research is analytical with a cross- sectional design. A sample of 92 respondents was taken using accidental sampling techniques using inclusion and exclusion criteria. Data were obtained by distributing family support questionnaires to referral patients and structured interviews for referring midwives to explore referral procedures. The data were analyzed using chi-squere tests and path analysis. Of the 92 referral cases, 57 respondents (61.9%) experienced delays in making decisions and 8 cases (8.7%) experienced delays in referrals. The results of statistical tests on predisposing factors were found to have no meaningful relationship with delays in maternal emergency referrals with a p value of > α 0.05. The results of the path analysis on 2 independent variables, namely family support and referral procedures for delays in decision making and their impact on referral delays showed varying results. There is a significant relationship in several pathways, namely: family support with late referrals, family support for late decision making, referral procedures with delays in decision making, delays in decision making with late referrals, referral procedures with delays in referrals, and family support and referral procedures for late referrals through delays in decision making with a value of p<0.05. Meanwhile, in several other pathways, no significant relationship (p>0.05) was obtained, namely: predisposing factors (age, education, income, parity, frequency of pregnancy examinations) to late referrals